ESTHETICS IN FIXED PARTIAL DENTURE PATIENTS VISITING A DENTAL HOSPITAL - Ganapathi, Amanthi; Ganapathy, Dhanaraj; .Jeevitha, M (International Journal of Psychosocial Rehabilitation, 2025)
Esthetics is a major concern during restoration of anterior partial edentulous areas. Controversy persists regarding the treatment planning criteria for esthetic restorations. Interdisciplinary treatment planning, biocompatibility, marginal adaptation, color matching, patient selection, technique sensitivity, and mode and rate of failure of tooth-colored restorations are all issues that need consideration prior to restoration of an anterior partially edentulous area.Patients’ perception of their oral health status are important outcomes in prosthodontics.There is increasing realization that patient evaluation regarding the satisfaction level is worth such treatment.The aim of the study is to evaluate the Fixed Partial Denture considering the esthetic outcome of the treatment.Male patients (52.9%)were higher when compared to the female patients and (46.9),transgender(0.13%). Fixed partial denture with poor esthetics accounts for 26%,Fair esthetics adds for 38.3% which is more when compared to others,Good Esthetics accounts for 35.6%.In this study there are esthetics concerns still addressed in patients with fixed partial denture..